The Role of Ceramides in Diabetes and Cardiovascular Disease Regulation of Ceramides by Adipokines - Field, Bianca C.; Gordillo, Ruth; Scherer, Philipp E. (Frontiers in Endocrinology, 2020)
Diabetes and cardiovascular disease are two diseases whose pathophysiology is intertwined with metabolic dysfunction. Recently, one particular lipid species has been shown to influence the development and sustainment of these diseases: ceramides. These lipid species are subtype of sphingolipids that are central in a number of different metabolic disturbances. Increased levels of ceramides are known to correlate with impaired cardiovascular and metabolic health. Furthermore, the interaction between ceramides and adipokines, most notably adiponectin and leptin, appears to play a role in the pathophysiology of these conditions. Adiponectin counteracts the detrimental effects of elevated ceramides, largely through activation of the ceramidase activity of its receptors. Elevated ceramides appear to worsen leptin resistance, which is an important phenomenon in the pathophysiology of obesity the associated metabolic syndrome.